2019
DOI: 10.1038/s41598-019-40994-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neonicotinoid Insecticides on Physiology and Reproductive Characteristics of Captive Female and Fawn White-tailed Deer

Abstract: Over the past decade, abnormalities have been documented in white-tailed deer (Odocoileus virginianus) in west-central Montana. Hypotheses proposed to explain these anomalies included contact with endocrine disrupting pesticides, such as imidacloprid. We evaluated the effects of imidacloprid experimentally at the South Dakota State University Wildlife and Fisheries Captive Facility where adult white-tailed deer females and their fawns were administered aqueous imidacloprid (an untreated control, 1,500 ng/L, 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…They act on receptor proteins of the insect nervous system. Many reports detail their insecticidal properties, but reports on bioaccumulation and its transfer into plant organs are minimal. In this context, the ability of Zea mays plant to accumulate THM in seeds and seedlings (roots, stem, and leaves) was confirmed at MSE using square‐wave voltammetry (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They act on receptor proteins of the insect nervous system. Many reports detail their insecticidal properties, but reports on bioaccumulation and its transfer into plant organs are minimal. In this context, the ability of Zea mays plant to accumulate THM in seeds and seedlings (roots, stem, and leaves) was confirmed at MSE using square‐wave voltammetry (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…They act on receptor proteins of the insect nervous system. Many reports detail their insecticidal properties, [26][27][28][29] but reports on bioaccumulation and its transfer into plant organs are minimal.…”
Section: Thiamethoxam Bioaccumulation In Zea Maysmentioning
confidence: 99%
“…[42] Imidacloprid administration at field-relevant doses in drinking water affects white tail deer and fawns. [43] Such findings in numerouss pecies includingl arger mammals increaset he urgency of developing efficient imidacloprid decontamination processes. Moving forward, we consider that this study adds to the case that TAML/peroxide systems have real potential forr emoving some of the most recalcitrant micropollutants from water and we are focusedo nm aking this happen.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to neonicotinoids can occur via different pathways, including pollen, nectar, guttation fluids, soil, air, and noncrop vegetation (Roubos et al 2014, Mogren and Lundgren 2016, Calvo-Agudo et al 2019, and sublethal and lethal effects have been reported for pollinators (Blacquière et al 2012, Whitehorn et al 2012, Rundlöf et al 2015 and natural enemies, potentially undermining vital pollination and biological control services (Pisa et al 2015, Calvo-Agudo et al 2019. High levels of exposure were reported for different species of farmland birds (Humann-Guilleminot et al 2019), and sublethal impacts have been reported for large vertebrates, such as deer (Gibbons et al 2015, Berheim et al 2019. Residues of neonicotinoids have been found in honey all over the world, at potentially harmful concentrations for nectar-feeding insects in 48% of the samples (Mitchell et al 2017).…”
Section: Crisis and Disastermentioning
confidence: 99%
“…Over the past years, there has been increasing concern over the broad environmental risks of neonicotinoid insecticides (EASAC 2015, Giorio et al 2017, Pisa et al 2017, Goulson 2018. Since their introduction in the 1990s, neonicotinoids have rapidly diffused because of their systemic mode of action (MoA), high efficiency at low doses, and their presumed low toxicity to vertebrates including humans (but see Cimino et al 2017, Berheim et al 2019. Today, neonicotinoids are the most widely used insecticides in the world, being employed in more than 120 countries and on 450 crops Tooker 2015, Simon-Delso et al 2015).…”
Section: Introductionmentioning
confidence: 99%